Areas of continuing education for pharmacists on the care of high-risk patients (One Health & Risk Management, 2025)
Introduction. The presence of qualified pharmacists in community pharmacies ensures that high-risk patient groups receive safe and effective pharmaceutical care when using pharmacy services.Material and methods. This study employed a descriptive methodology. The research tool is a questionnaire, which includes 16 questions that describe to respondents’ characteristics and assess respondents’ attitudes toward continuous training in specialized fields. The number of respondents was 406. Data processing were performed using Excel software.Results. The majority of respondents (64,06%, CI95: 59,37-68,7) believe that there is a frequent need for improving knowledge in the field of geriatrics, and 82.86% (CI95: 79,53-85,99) of respondents fully agree that the community pharmacists should be well-informed in pediatrics. Pharmacists are aware of the responsibility they bear towards these categories of patients in community pharmacies and believe it is beneficial (63,01%, CI95: 58,35-67,74) for them to periodically update their knowledge in specialized pharmaceutical care, covering a variety of topics.Conclusions. Pharmacists’ views emphasized the importance of enhancing their professional training in delivering specialized pharmaceutical services. These findings support the development and implementation of the course “Specialized Pharmaceutical Assistance for High-Risk Patients” within pharmacists’ continuing education programs.